ANALISIS POTENSI WISATA BERBASIS KOMUNITAS DI KECAMATAN SANGALLA UTARA, KABUPATEN TANA TORAJA - Maisandrya, Riska; Wuisang , Cynthia; Warouw, Fela (Universitas Bina Taruna Gorontalo, 2024)
This research aims to identify the elements of Community Based Tourism (CBT) in North Sangalla District, Tana Toraja Regency and determine the strategy for developing community based tourism potential. This research uses a descriptive method with a qualitative approach based on SWOT Analysis. The required data, both primary data and secondary data, was obtained through data collection from related agencies as well as literature studies, interviews, field observations, and documentation. The results of this research are based on the identification of CBT elements in North Sangalla District, Tana Toraja Regency, it is known that (1) the elements of CBT ini North Sangalla District are natural and cultural resources, organization, management, and learning. (2) the existing tourism potential development strategy can be implemented by prioritizing the development of natural resource potential and the development of attractioness. The conclusion from the research conducted is that good collaboration and cooperation is needed between the goverment and the community. The goverment can work together with educational institutions to improve the quality of human resources while the community needs to be actively involved in creating autentic tourism experinces, developing tourist attractions and managing local businesses. This synergy will support sustainable tourism development and increase tourist attraction.